The negative footprint illusion in environmental impact estimates: Methodological considerations - Sörqvist, Patrik; Holmgren, Mattias (Frontiers in Psychology, 2022)
Past research has consistently shown that carbon footprint estimates of a set of conventional and more environmentally friendly items in combination tend to be lower than estimates of the conventional items alone. This ‘negative footprint illusion’ is a benchmark for the study of how cognitive heuristics and biases underpin environmentally significant behavior. However, for this to be a useful paradigm the findings must also be reliable and valid, and an understanding of how methodological details such as response time pressure influence the illusion is necessary. Past research has cast some doubt as to whether the illusion is obtained when responses are made on a ratio/quantitative scale and when a within-participants design is used. Moreover, in past research on the negative footprint illusion, participants have had essentially as much time as they liked to make the estimates. It is yet unknown how time pressure influences the effect. This paper reports an experiment that found the effect when participants were asked to estimate the items’ emissions in kilograms CO2 (a ratio scale) under high and under low time pressure, using a within-participants design. Thus, the negative footprint illusion seems to be a reliable and valid phenomenon that generalizes across methodological considerations and not an artifact of specific details in the experimental setup.